Carbon-coated silicon-based composite material as well as preparation method and application thereof
By preparing carbon-covered silicon-based composite materials, the problems of low conductivity and volume expansion of silicon oxide are solved, and a lithium-ion battery negative electrode material with high conductivity and excellent circulation performance are achieved.
Patent Information
- Application Number
- CN202411875175.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silicon oxide, as a negative electrode material for lithium-ion batteries, has problems of low conductivity and volume expansion, which limits its practical application.
The carbon-covered silicon-based composite material is prepared by a preparation method of a carbon-covered silicon/silica/lithium silicate composite material with a double protective layer is formed through liquid phase mixing, high-temperature sintering and carbonization processes.
The conductivity and cyclic performance of the composite material are improved, the volume expansion during the charging and discharging process is suppressed, and the first charging and discharging efficiency and capacity retention rate are improved.
Smart Images

Figure CN119650655A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a carbon-coated silicon-based composite material and a preparation method and application thereof. Background Art
[0002] The continuous development and progress of today's battery technology is essential for energy storage and the utilization of renewable resources. As a potential negative electrode material, silicon dioxide (SiO) has attracted extensive research interest. Traditional lithium-ion battery negative electrode materials such as graphite have certain limitations in energy density and capacity, while silicon dioxide has a higher theoretical specific capacity and lower price, so it is considered to be a potential alternative material in lithium-ion batteries.
[0003] Silicon oxide has many advantages as a negative electrode material. First, due to its high theoretical specific capacity (2600mAh / g), silicon oxide can provide a higher energy storage density, allowing the battery to have a longer battery life. Secondly, the price of silicon oxide is relatively low, and it is more economical than traditional graphite materials. In addition, silicon oxide has good chemical stability, which gives it broad application prospects in the battery field.
[0004] However, there are still some challenges in the practical application of silicon oxide materials. First, the electrical conductivity of silicon oxide is relatively low, resulting in slow discharge and charge rates of the battery. Second, silicon oxide is prone to volume expansion during the insertion and extraction of lithium ions, resulting in fracture and failure of the material. These problems limit the practical application of silicon oxide materials and require further research to solve. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a carbon-coated silicon-based composite material and a preparation method and application thereof.
[0006] The present invention provides a method for preparing a carbon-coated silicon-based composite material, comprising the following steps:
[0007] S1, mixing a lithium source and a silicon oxide material in a solvent, then evaporating to remove the solvent, and sintering at a high temperature under a protective atmosphere to obtain a silicon oxide / lithium silicate precursor;
[0008] S2, mixing the silicon dioxide / lithium silicate precursor with an organic resin in a solvent, then evaporating the solvent to remove the solvent, and carbonizing at high temperature under a protective atmosphere to obtain.
[0009] Preferably, the particle size D50 of the silicon oxide material is 4 to 8 μm; the organic resin is phenolic resin, epoxy resin or a combination thereof; the lithium source is at least one of lithium hydroxide monohydrate and lithium carbonate; and the solvent is at least one of water and ethanol.
[0010] Preferably, the molar ratio of lithium element in the lithium source to silicon oxide is (0.04-0.2):1; preferably, the molar ratio of lithium element in the lithium source to silicon oxide is (0.05-0.15):1, specifically 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.10:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, 0.15:1.
[0011] Preferably, in S1, high temperature sintering includes: heating to 450°C to 550°C at a heating rate of 2 to 5°C / min, and keeping the temperature for 0.5h to 6h.
[0012] Preferably, in S1, the solvent is water; preferably, in S1, the ratio of silicon dioxide to the solvent is 1 g: (0.5-1) mL.
[0013] Preferably, in S1, the method for evaporating and removing the solvent comprises: first heating and stirring to a slurry state, and then drying in a vacuum oven for more than 6 hours; preferably, the heating and stirring temperature is 80°C to 100°C.
[0014] Preferably, in S2, high temperature carbonization comprises: heating to 880°C to 920°C at a heating rate of 2 to 5°C / min, and keeping the temperature for 0.5h to 6h.
[0015] Preferably, in S2, the solvent is water; preferably, in S2, the ratio of silicon dioxide / lithium silicate precursor to the solvent is 1 g: (0.5-1) mL.
[0016] Preferably, in S2, the method for evaporating and removing the solvent comprises: first heating and stirring to a slurry state, and then drying in a vacuum oven for more than 6 hours; preferably, the heating and stirring temperature is 80°C to 100°C.
[0017] Preferably, the carbon content in the carbon-coated silicon-based composite material is 3% to 5%.
[0018] Preferably, the particle size D50 of the carbon-coated silicon-based composite material is 4 to 8 μm.
[0019] In the present invention, after the high-temperature sintering of S1, conventional post-processing steps may be further included, such as washing, drying, grinding, and screening.
[0020] In the present invention, after the high-temperature carbonization of S2, conventional post-processing steps may also be included, such as washing, drying, grinding, and screening.
[0021] In the present invention, the protective atmosphere refers to a non-reactive gas atmosphere, and the non-reactive gas is preferably at least one of nitrogen, argon and helium.
[0022] The invention also provides a carbon-coated silicon-based composite material, which is prepared by the preparation method.
[0023] The present invention also proposes the use of the carbon-coated silicon-based composite material as a negative electrode material for lithium-ion batteries.
[0024] The beneficial effects of the present invention are as follows:
[0025] The present invention first mixes silicon oxide material with lithium source liquid phase by liquid phase mixing followed by solvent evaporation, and evenly distributes a layer of lithium silicate precursor on the surface of silicon oxide particles by high-temperature sintering; then mixes it with organic resin liquid phase so that the surface of its particles is evenly coated with a layer of organic resin, and after a high-temperature carbonization process, silicon oxide undergoes a disproportionate reaction to obtain silicon and silicon dioxide, and the resin layer on the outer surface is carbonized into graphite carbon to coat the silicon / silicon dioxide inside, i.e., carbon-coated silicon / silicon dioxide / lithium silicate composite material (Si / SiO2 / Li2Si2O5). First, the mixing method of solvent evaporation after liquid phase mixing is more uniform than the powder mixing method, making the coating layer on the surface of the material particles more uniform; secondly, after generating a double protective layer of lithium silicate layer and carbon layer, the volume expansion during the charge and discharge process can be effectively suppressed, and the graphite carbon layer can increase the conductivity of the composite material, so that the composite material has excellent cycle performance and rate performance; in addition, the generation of the lithium silicate layer can isolate the interface contact between the silicon-based composite material and the electrolyte, avoiding the further generation of SEI film and the consumption of lithium ions during the first lithium insertion, so that the composite material has a higher first charge and discharge efficiency. Finally, the preparation method of the carbon-coated silicon-based composite material provided by the present invention has simple preparation conditions, is safe, and is easy to operate and industrialize.
[0026] The carbon-coated silicon-based composite material prepared by the method of the present invention has a reversible specific capacity of up to 906.13 mAh / g, an initial charge and discharge efficiency of up to 85.1%, and a capacity retention rate of up to 97.28% after 80 charge and discharge cycles. It has a high initial coulombic efficiency and excellent cycle performance and rate performance. In addition, the method of the present invention has a simple preparation process and is industrializable. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the preparation method of the carbon-coated silicon-based composite material of the present invention.
[0028] Figure 2 This is a scanning electron microscope (SEM) image of the carbon-coated silicon-based composite material prepared by the method of Example 1 of the present invention.
[0029] Figure 3 This is the X-ray diffraction pattern (XRD) of the carbon-coated silicon-based composite material prepared by the method of Example 1 of the present invention.
[0030] Figure 4 This is a cyclic voltammetry (CV) curve of the carbon-coated silicon-based composite material prepared by the method of Example 1 of the present invention at 0.1 mA / s.
[0031] Figure 5 This is a graph showing the first charge and discharge curve of the carbon-coated silicon-based composite material prepared by the method of Example 1 of the present invention at 0.15 A / g.
[0032] Figure 6 This is a charge and discharge cycle diagram of the carbon-coated silicon-based composite material prepared by the method of Example 1 of the present invention at 0.15 A / g.
[0033] Figure 7 This is a rate performance diagram of the carbon-coated silicon-based composite material prepared by the method of Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is described in detail below through specific embodiments.
[0035] Example 1
[0036] A carbon-coated silicon-based composite material and a preparation method thereof, comprising the following steps:
[0037] S1. Weigh 2 g (0.04766 mol) of lithium hydroxide monohydrate, add 25 mL of water to disperse evenly, add 36 g of silicon dioxide material with a particle size D50 of 4 to 8 μm, stir and mix at room temperature for 30 min, then heat and stir at 80 ° C to evaporate the solvent to a slurry, transfer to a vacuum oven at 80 ° C and dry for 6 h, then transfer to an Al2O3 crucible, cover the crucible with a lid and place it in a tubular furnace, pass argon protection, heat to 500 ° C at a rate of 5 ° C / min, keep warm for 1 h and then cool naturally, take out the material and grind it in an air atmosphere, then sieve it through a 325 mesh filter to obtain a silicon dioxide / lithium silicate precursor;
[0038] S2. Weigh 36 g of silicon dioxide / lithium silicate precursor, add 25 mL of water to disperse evenly, stir at room temperature for 30 min, then add 5 g of phenolic resin, stir and mix on a magnetic stirrer at room temperature for 2 h, then heat and stir at 80 ° C to evaporate the solvent to a slurry, transfer to a vacuum oven at 80 ° C and dry for 6 h, then transfer to an Al2O3 crucible, cover the crucible with a lid and place it in a tubular furnace, pass argon protection, heat to 900 ° C at a rate of 5 ° C / min, keep warm for 2 h and then cool naturally, take out the material, grind it in an air atmosphere, wash with water until the supernatant is neutral, and grind it to a carbon-coated silicon-based composite material with a D50 of 4-8 um after drying.
[0039] The prepared composite materials were characterized and tested by using X-ray diffractometer (XRD), scanning transmission microscope (SEM) and electrical tester. Figure 1 The figure shows the principle schematic diagram of the silicon-based composite material synthesized by the method of the present invention. The raw material silicon oxide is mixed with a lithium source and sintered at high temperature, and a layer of lithium silicate is coated on the surface of the particles. After being mixed with an organic resin and carbonized at high temperature and undergoing a disproportionation reaction, a layer of carbon is coated on the outermost layer. Figure 2 As shown in the figure, the particles of the silicon-based composite material are relatively uniform, without impurities, and the particle size D50 is about 5.5um. Figure 3 The results show that the synthesized silicon-based composite material is consistent with the Si / SiO2 / Li2Si2O5 standard PFD card, in which silicon and silicon dioxide are obtained by partial disproportionation reaction of silicon oxide, and lithium silicate is obtained by further reaction of silicon oxide / lithium silicate precursor during high temperature carbonization. It is proved that this composite material is composed of silicon, silicon dioxide and lithium silicate. The composite material was subjected to electrochemical testing. Figure 4 The CV curve obtained by cyclic voltammetry test is shown in the figure. In the first scan, current peaks appear at about 0.6V and 1.3V, which is mainly due to the formation of SEI film and the decomposition of part of the electrolyte. After 5 cycles, it is basically stable. The coulombic efficiency, cycle performance and rate performance of the composite material are tested by assembling a 2032-type button half-cell with lithium metal as the positive electrode and silicon-based composite material as the negative electrode. Figure 5 The figure shows the first charge-discharge curve obtained by discharging to 0.005V at 0.15A / g and 0.03A / g and then charging to 2V at 0.15A / g. The first charge specific capacity is 906.13mAh / g and the first coulombic efficiency is 85.1%. Figure 6 As shown, after 80 charge and discharge cycles, the capacity retention rate is still 97.28%, which is mainly due to the coating of lithium silicate and carbon layer, which inhibits the expansion of silicon oxide embedded lithium and improves the cycle performance. Figure 7 This is the rate performance diagram. The carbon layer after high-temperature carbonization provides a certain conductivity and can provide more electron transmission channels, so that it still has a higher capacity during charging and discharging at a high current density. When it is expanded 20 times to 2A / g, the charging capacity is increased by 400mAh / g.
[0040] Example 2
[0041] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 2 are different from those in Example 1 in that the mass of lithium hydroxide monohydrate in step S1 is changed to 3 g (0.07150 mol), and the other steps are the same as in Example 1.
[0042] Example 3
[0043] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 3 are different from those in Example 1 in that the mass of lithium hydroxide monohydrate in step S1 is changed to 4 g (0.09533 mol), and the other steps are the same as in Example 1.
[0044] Example 4
[0045] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 4 are different from those in Example 1 in that 2 g of lithium hydroxide monohydrate in step S1 is replaced with 2 g of lithium carbonate, and the other steps are the same as those in Example 1.
[0046] Example 5
[0047] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 5 are different from those in Example 1 in that the heating rate in step S1 is changed to 2°C / min, and the other steps are the same as in Example 1.
[0048] Example 6
[0049] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 6 are different from those in Example 1 in that the heating rate in step S2 is changed to 2°C / min, and the other steps are the same as in Example 1.
[0050] Example 7
[0051] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 7 are different from those in Example 1 in that the insulation time in step S1 is changed to 6 hours, and the other steps are the same as in Example 1.
[0052] Example 8
[0053] A carbon-coated silicon-based composite material and a preparation method thereof as described in Example 8 are different from those in Example 1 in that the insulation time in step S2 is changed to 6 hours, and the other steps are the same as in Example 1.
[0054] Comparative Example 1
[0055] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 1 are different from those in Example 1 in that the mass of lithium hydroxide monohydrate in step S1 is changed to 1 g (0.02383 mol), and the other steps are the same as those in Example 1.
[0056] Comparative Example 2
[0057] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 2 are different from those in Example 1 in that the high-temperature carbonization temperature in step S2 is changed to 850° C., and the other steps are the same as in Example 1.
[0058] Comparative Example 3
[0059] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 3 are different from those in Example 1 in that the high-temperature carbonization temperature in step S2 is changed to 960° C., and the other steps are the same as in Example 1.
[0060] Comparative Example 4
[0061] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 5 are different from those in Example 1 in that the high-temperature treatment temperature in step S1 is changed to 600° C., and the other steps are the same as in Example 1.
[0062] Comparative Example 5
[0063] The carbon-coated silicon-based composite material and the preparation method thereof described in Comparative Example 5 are different from those in Example 1 in that the high-temperature treatment temperature in step S1 is changed to 700° C., and the other steps are the same as those in Example 1.
[0064] Comparative Example 6
[0065] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 6 are different from those in Example 1 in that the high-temperature treatment temperature in step S1 is changed to 850° C., and the other steps are the same as in Example 1.
[0066] Comparative Example 7
[0067] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 7 are different from those in Example 1 in that the mass of the phenolic resin in step S3 is changed to 15 g, and the other steps are the same as in Example 1.
[0068] Comparative Example 8
[0069] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 8 are different from those in Example 1 in that the mass of the phenolic resin in step S3 is changed to 10 g, and the other steps are the same as in Example 1.
[0070] Comparative Example 9
[0071] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 9 are different from those in Example 1 in that the mass of the phenolic resin in step S3 is changed to 7.5 g, and the other steps are the same as in Example 1.
[0072] Comparative Example 10
[0073] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 10 are different from those in Example 1 in that the mass of the phenolic resin in step S3 is changed to 3.33 g, and the other steps are the same as in Example 1.
[0074] Comparative Example 11
[0075] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 11 are different from those in Example 1 in that the mass of the phenolic resin in step S3 is changed to 1.66 g, and the other steps are the same as in Example 1.
[0076] Comparative Example 12
[0077] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 12 are different from those in Example 1 in that 2 g of lithium hydroxide monohydrate in step S1 is replaced with 2 g of lithium chloride, and the other steps are the same as those in Example 1.
[0078] Comparative Example 13
[0079] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 13 are different from those in Example 1 in that in step S1: 2 g (0.04766 mol) of lithium hydroxide monohydrate is weighed, mixed with 36 g of silicon dioxide material with a particle size D50 of 4 to 8 μm, and then fully ball-milled at a speed of 180 rpm for 2 h, and then transferred to an Al2O3 crucible, covered with a crucible lid and placed in a tubular furnace, and argon gas is introduced for protection, and the temperature is raised to 500°C at a rate of 5°C / min, kept warm for 1 h, and then naturally cooled, the material is taken out and ground in an air atmosphere, and then sieved through a 325-mesh filter to obtain a silicon dioxide / lithium silicate precursor, and the other steps are the same as in Example 1.
[0080] Comparative Example 14
[0081] A carbon-coated silicon-based composite material and a preparation method thereof as described in Comparative Example 14 differ from Example 1 in that in step S2: 36 g of silicon dioxide / lithium silicate precursor is weighed, mixed with 5 g of phenolic resin, and then fully ball-milled at a speed of 180 rpm for 2 h, and then transferred to an Al2O3 crucible, covered with a crucible lid and placed in a tubular furnace, argon gas is introduced for protection, the temperature is raised to 900°C at a rate of 5°C / min, kept warm for 2 h, and then naturally cooled, the material is taken out and ground in an air atmosphere, and washed with water until the supernatant is neutral, and then ground after drying to a carbon-coated silicon-based composite material with a D50 of 4-8 um.
[0082] The carbon-coated silicon-based composite material of the above embodiment and comparative example is used as the negative electrode material of the lithium-ion battery. The slurry is made according to the mass ratio of silicon-based composite material, sodium carboxymethyl cellulose and conductive carbon black of 8:1:1, and then coated on copper foil, dried and cut into 12mm diameter discs to obtain the positive electrode. Lithium metal is used as the negative electrode to assemble into a 2032 button half-cell, and then discharged to 0.005V at 0.15A / g and 0.03A / g constant current, and charged to 2V at 0.15A / g constant current to obtain the first coulomb efficiency and charge-discharge specific capacity. After continuing to cycle for 80 times, the capacity retention rate is obtained. In addition, the carbon content and particle size are measured using a carbon-sulfur meter and a particle size analyzer. The test data are shown in Table 1:
[0083] Table 1
[0084]
[0085] In summary, the composite material of the present invention has a simple preparation process and is industrializable. When used as a negative electrode material for lithium-ion batteries, it has a high first coulombic efficiency and excellent cycle performance and rate performance.
[0086] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated silicon-based composite material, characterized in that: The following steps are involved: S1, mixing a lithium source and a silicon oxide material in a solvent, then evaporating to remove the solvent, and sintering at a high temperature under a protective atmosphere to obtain a silicon oxide / lithium silicate precursor; S2, mixing the silicon dioxide / lithium silicate precursor with an organic resin in a solvent, then evaporating the solvent to remove the solvent, and carbonizing at high temperature under a protective atmosphere to obtain.
2. The method for preparing the carbon-coated silicon-based composite material according to claim 1, characterized in that: The particle size D50 of the silicon oxide material is 4 to 8 μm; the organic resin is phenolic resin, epoxy resin or a combination thereof; and the lithium source is at least one of lithium hydroxide monohydrate and lithium carbonate.
3. The method for preparing the carbon-coated silicon-based composite material according to claim 1, characterized in that: The molar ratio of lithium element to silicon oxide in the lithium source is (0.04-0.2):
1.
4. The method for preparing the carbon-coated silicon-based composite material according to claim 1, characterized in that: In S1, the high temperature sintering includes: heating to 450°C to 550°C at a heating rate of 2 to 5°C / min, and keeping the temperature for 0.5h to 6h.
5. The method for preparing the carbon-coated silicon-based composite material according to claim 1, characterized in that: In S2, high temperature carbonization includes: heating to 880°C to 920°C at a heating rate of 2 to 5°C / min, and keeping the temperature for 0.5h to 6h.
6. The method for preparing the carbon-coated silicon-based composite material according to claim 1, characterized in that: The carbon content in the carbon-coated silicon-based composite material is 3% to 5%.
7. The method for preparing the carbon-coated silicon-based composite material according to claim 1, characterized in that: The particle size D50 of the carbon-coated silicon-based composite material is 4 to 8 μm.
8. A carbon-coated silicon-based composite material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the carbon-coated silicon-based composite material according to claim 8 as a negative electrode material for lithium-ion batteries.
Citation Information
Patent Citations
Space buffer lithium-doped silicon oxide composite material, preparation method of composite material and lithium ion battery
CN108232145A
Carbon-coated silicon-based negative electrode material and preparation method thereof
CN112164779A
Carbon-coated pre-lithiated silicon-based composite material, multi-phase composite material and preparation method
CN116742003A
Pre-magnesium silicon-oxygen negative electrode material of lithium ion battery and preparation method of pre-magnesium silicon-oxygen negative electrode material
CN117855434A
Pre-lithiated silicon monoxide prepared by carbon-coated low-temperature molten salt technology and application of pre-lithiated silicon monoxide in energy storage battery
CN118598143A